Successful Regression in Patients with Progressive Keratoconus by Corneal Crosslinking - Röck, Tobias; Konrad, Eva-Maria; Röck, Daniel; Bramkamp, Matthias; Blumenstock, Gunnar; Bartz-Schmidt, Karl Ulrich (Klinische Monatsblätter für Augenheilkunde, 2021)
Background Since 2019, corneal collagen crosslinking (CXL) is included in the catalog of procedures covered by statutory health insurance in Germany. CXL is an established ophthalmological procedure for the last 20 years. The aim of this investigation was the measurement of progression before and after CXL.Material und Methods 65 consecutive eyes with progressive keratoconus from 53 patients were included in the retrospective study, which were observed at the University Eye Hospital Tübingen at least two years before and at least two years after CXL. The time of observation took place from October 2009 until March 2018. Parameters of interest had been the best corrected visual acuity (BCVA) and the keratometric values from the elevation maps measured by a Scheimpflug camera.Results 65 eyes of 53 patients had been documented. The study population included 46 (86.8%) male and 7 (13.2%) female subjects. The mean age was 24 ± 8 years. The averaged observation time between the primary consultation and CXL showed 25 ± 15 months. Preoperatively the mean BCVA pointed out in a significant increase (0.13 ± 0.17 [first visit] vs. 0.23 ± 0.22 [preOP], p < 0.0001) while the mean Kmax resulted in a statistically significant increase (46.34 ± 3.33 dpt [first visit] vs. 48.78 ± 4.17 dpt [preOP], p < 0.0001). The mean thinnest point of the cornea showed a significant decrease (490.48 ± 34.23 µm [first visit] vs. 468.62 ± 29.84 µm [preop], p < 0.0001). Postoperatively the mean BCVA resulted in a significant improvement at the 12th postoperative month in comparison to the preoperative measurement (0.23 ± 0.22 [preOP] vs. 0.16 ± 0.14 [12 months], p = 0.04 respectively 0.17 ± 0.17 [24 months], p = 0.0006). The mean Kmax demonstrated in the 12th postoperative month a significant reduction (48.78 ± 4.17 dpt [preOP] vs. 47.91 ± 3.41 dpt [12 months], p = 0.0009 respectively 48 ± 4.56 dpt [24 months], p = 0.0051). The mean thinnest point of the cornea indicated a decrease at the 12th postoperative month (468.62 ± 29.84 µm [preOP] vs. 459.82 ± 35.88 µm [12 months], p = 0.0078 respectively 453.47 ± 43.39 µm [24 months], p = 0.0227).Conclusion CXL is a successful procedure for the therapy of progressive keratoconus.
Keywords: corneal crosslinking; cornea; keratoconus; regression; keratometry